A Prototype for the analysis of Conflict resolving Algorithms in Context aware Environment using simulation (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper we are proposing a GUI based Prototype for user centered environment like class room, library hall, laboratory, meeting hall, coffee shop, kitchen, living room and bedroom, which recommends useful services based on the user’s context. Service recommendation is mainly based on parameters such as user, location, time, day and mood. In addition whenever the conflict arises among different users it will be resolved using some conflict resolving algorithms. The motivation behind the proposed work is to improve the user satisfaction level and to improve the social relationship between user and devices The prototype contains simulated sensors which are used to capture the raw context information, which is then described with meaningful English sentence and services are recommended based on user’s situation. The proposed conflict resolving algorithms are Rule based algorithm, Bayesian probability based algorithm and Rough set theory based algorithm. The amount of conflicts resolved by these algorithms is also analyzed at the end.